Karakteristik kwetiau kering dengan bahan baku tepung beras dan tepung talas hitam terfementasi - Yuliana Erning Indrastuti; Susana Susana; Dodi Iskandar; Tata Yudi Wardhana; Sasmidi Sasmidi (Agroindustrial Technology, University of Trunojoyo Madura, 2023)
The purpose of this study was to investigate the effect of the proportions of rice flour and black taro flour on the characteristics of rice noodle (kwetiau). Kwetiau were produced by blending various proportions of rice and black taro flour (100:0; 75:25; 50:50; 25:75; 0;100) which were evaluated for water content, texture, cooking quality and color. The results indicated that proportion of rice and black taro flour affects the cooking quality, texture and color of the kwetiau (p0,01). Black taro flour addition produced kwetiau with decreased cooking time, hardness, cohesivennes and chewiness, L* value and a* value. A higher proportion of black taro flour increased the weight after cooking, cooking loss, adhesiveness and b* of the kwetiau. The proportion of rice and black taro flour did not affect the moisture content and springiness. Fermented black taro flour can be used to a limited extent (25 %) as a substitute for rice flour in making kwetiau.